Genetic analysis of compound heterozygous pathogenic variants of the F11 gene in two Chinese patients with hereditary factor XI deficiency. Issue 1 (January 2022) - Wang, Huanhuan; Jiang, Shuting; Xie, Haixiao; Yang, Lihong; Jin, Yanhui; Wang, Mingshan
Abstract : N/A: The aim of this study was to explore the molecular pathogenesis of two families with compound heterozygous hereditary factor XI deficiency. All the exons, flanking sequences, 5' and 3' untranslated regions of the F11 gene were analysed by direct DNA sequencing. The suspected variants were confirmed by reverse sequencing. Bioinformatics softwares were used to analysis the conservation and the possible impact of these pathogenic variants. Genetic analysis revealed c.689G > T and c.1556G > A variants of F11 gene in family A; c.1107C > A and c.1557G > C variants of F11 gene in family B. These variants sites were highly conserved among homologous species. Bioinformatics and structural analysis demonstrated these variants were pathogenic and could affect the protein structure. The c.689G > T, c.1556G > A, c.1107C > A and the c.1557G > C heterozygous variants might be responsible for the decrease of FXI levels in probands. In addition, c.689G > T (NM_000128.4) is a novel pathogenic variant site, which has not been reported.